Firm Characteristics, Relative Efficiency, and Equity Returns - Nguyen, Giao X.; Swanson, Peggy E. (Journal of Financial and Quantitative Analysis, 2009)
Abstract This study uses a stochastic frontier approach to evaluate firm efficiency. The resulting efficiency score, based on firm characteristics, is the input for performance evaluation. The portfolio composed of highly efficient firms significantly underperforms the portfolio composed of inefficient firms even after adjustment for firm characteristics and risk factors, suggesting a required premium for the inefficient firms. The difference in performance between the two portfolios remains for at least five years after the portfolio formation year. In addition, firm efficiency exhibits significant explanatory power for average equity returns in cross-sectional analysis.